A modified endaural approach to the fractured condyle: a clinical case report - Silva Cardoso, Lais Inês; Ramos de Brito, Ana Caroline; da Silva Rodrigues Freire , Simei André; Luiz de Freitas , Paulo Henrique; da Costa Ribeiro , Renato (Brazilian Journal of Case Reports, 2021)
The authors present a modified endaural incision with a caudal extension for surgical access to the mandibular condyle. The approach combined the advantages of good scar cosmesis and sufficient access to the surgical site for optimal placement of the osteosynthesis with lesser risk of nerve damage.